The Impact of The Digital Transformation Led by Vision 2030 On the Saudi Economy - Alkhalifah, Nouf (International Journal of Psychosocial Rehabilitation, 2020)
In the midst of the ever-changing socioeconomic environment, Saudi Arabia’s 2030 vision, which was conceptualized in 2016, continues to shape the modernization of the country’s economic prosperity and the social fabric of Saudi society (Surf & Mostafa, 2017). Following the 2003 to 2013 oil boom that led to the vast growth in the Saudi economy, almost doubling in size, that led to over 1.7 million jobs created in Saudi Arabia with 75% adjusted inflation growth and over $450 billion invested in education, infrastructure, and health (Abdelfattah, 2017). Based on the context of the 2030 vision based on economic expansion and improving the living standards and quality of Saudi Arabians, the authorities developed a growth model that was dependent on public spending and oil exports. Despite such ambitious development plans and modernization of Saudi Arabia, there have been significant concerns about the depletion of its oil for exports that it depends on for the realization of its 2030 vision (Al-Zahrani, 2015). Thus, there have been significant suggestions on the impact of digital transformation and the vision 2030 would have on the Saudi Arabian economy.As globalization continues to shape the socioeconomic and the labor environment in Saudi Arabia, there are some factors that the current study aims to articulate and assess their future implications on Saudi Arabia’s economy. There have been concerns about the future of Saudi’s economy, with significant concerns being raised about the possible depletion of oil as its primary export production and means of foreign earnings (Abdelfattah, 2017). Thus, investment in infrastructure and technology such as digital transformation are the critical pillars of Vision 2030. The paper aims to articulate the impact of the digital transformation led by Vision 2030 on the Saudi economy and assess the future orientation of such digital transformation in achieving the 2030 vision objectives.